Enhancement of coupled surface / subsurface flow models in watersheds: analysis, model development, optimization, and user accessibility - Park, Seonggyu, author; Bailey, Ryan T., advisor; Grigg, Neil S., committee member; Ronayne, Michael J., committee member; Sale, Thomas, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.
Zip file contains supplementary video, no sound.
Keywords: MODFLOW; water resource; SWAT; integrated hydrologic model